Better than Average – The Positive Effects of a Department actively supporting Open Access - Kullman, Lars; Gilbert, Jonas (Septentrio Conference Series, 2014)
Chalmers University of Technology adopted an Open Access policy in 2010, mandating its researchers to deposit copies of their work in the university repository (Chalmers Publication Library). The Library was given the assignment to implement the policy but also to monitor the progress. In the beginning of 2013 we compiled the first comprehensive report to the university management and the departments. The share of Open Access publications varies to a large degree between different departments and subject fields. The reaction from the departments when presented to the numbers also varies, from referring to ‘the usual suspects’ – workflow issues, copyright issues, didn’t remember etc – to the reaction: how can we improve us? The Department of Signals and Systems publishes approx. 100 peer-reviewed journal articles and 200 peer-reviewed conference papers yearly. The Department started an active discussion how to improve the rate of Open Access. This discussion resulted in a project together with the library, in order to increase the number of Open Access publications and the visibility of the researchers and their publications on the web. The aim was to bring the share of Open Access publications from about 30 % to 100 %. An agreement with the Library was signed, where the library would assist the researchers to submit their papers to the repository. The proposed poster will discuss: a) How we provide feedback to management and departments. b) The differences between departments when it comes to Open Access publications. c) The importance of a department management actively promoting Open Access. d) How library and department collaborates in order to increase the amount of Open Access publications. e) Outcome and lessons learned from such collaboration. We hope to contribute to and participate in the discussion on what best practice the library should adopt to evaluate the progress of the transition to an open access culture among researchers.